2022
DOI: 10.14313/jamris/4-2021/28
|View full text |Cite
|
Sign up to set email alerts
|

Resource Optimisation in Cloud Computing: Comparative Study of Algorithms Applied to Recommendations in a Big Data Analysis Architecture

Abstract: Recommender systems (RS) have emerged as a means of providing relevant content to users, whether in social networking, health, education, or elections. Furthermore, with the rapid development of cloud computing, Big Data, and the Internet of Things (IoT), the component of all this is that elections are controlled by open and accountable, neutral, and autonomous election management bodies. The use of technology in voting procedures can make them faster, more efficient, and less susceptible to security breaches.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A genetic algorithm based on such a model is then used to optimize energy allocation, match the user thermal constraints, and allow the mixed-integer deterministic optimization algorithm to determine the remaining energy management actions. Consequently, a more integral vision is needed to provide accurate models of energy used in buildings [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Related Workmentioning
confidence: 99%
“…A genetic algorithm based on such a model is then used to optimize energy allocation, match the user thermal constraints, and allow the mixed-integer deterministic optimization algorithm to determine the remaining energy management actions. Consequently, a more integral vision is needed to provide accurate models of energy used in buildings [21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Related Workmentioning
confidence: 99%
“…Machine learning and deep learning have gained signi icant attention in recent years, leading to extensive research in this ield. However, most of the work in automated clinical code generation has been conducted on limited dummy data [9,10,39,62]. To address this, recent techniques have been developed for layered prediction and classi ication of real-world datasets, leveraging the sparsity of output codes [9,10,39].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Özeren and Top [12] investigated the effects of AR on student engagement, achievement, and immersion in science education. Their study demonstrated that AR can create interactive and immersive learning experiences that foster deeper student engagement and improved academic performance [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%